Tingkat Kelangsungan Hidup Planlet Kappaphycus alvarezii Pada Wadah Budidaya Berbeda Di Teluk Gerupuk Lombok Tengah - Utami, Wiyat Zahroh Sepia; Cokrowati, Nunik; Sumsanto, Muhammad; Rusman, Rusman (Fakultas Perikanan Universitas Pekalongan, 2024)
Seaweed producing areas in Indonesia include the Central Lombok region in Gerupuk Bay, Central Lombok, West Nusa Tenggara. Cultivation activities still have constraints on the availability of seaweed seeds that are limited and only available in certain seasons. To meet the needs of seaweed seeds can use seedlings from tissue culture. Tissue culture is an explant (talus) culture that is carried out aseptically and sterile in a solid medium that is added with Growth Regulators (ZPT) to be able to regenerate to multiply into a complete new plant. The advantages of using tissue culture seedlings are faster growth rates, strong talus, many branches, and higher levels of disease resistance. However, the obstacle in using tissue culture seedlings is their small size. The purpose of this study was to analyze the growth of K. alvarezii seaweed planlets cultivated with different containers. The research method used a complete randomized design consisting of 4 treatments with 3 replications. P1 (bottle container), P2 (plastic bag container), P3 (basket), P4 (waring). The results of this study were the best growth in this study was the P2 treatment using plastic bags with an absolute weight of 0.89 g, and a specific growth rate of 0.77%. and the best tissue slices were also in the P2 treatment using plastic bags. The lowest growth in this study was in the P3 treatment (basket) with a weight of -0.06 g and a specific growth rate of 0.47%. The conclusion of this study is the best planlet growth in the P2 treatment using plastic bags.